Relationship Between Heart Rate, Oxygen Consumption, and Energy Expenditure in Futsal - Silva, Henrique Santos da; Nakamura, Fabio Yuzo; Papoti, Marcelo; da Silva, Alexsandro Santos; Dos-Santos, Julio Wilson (Frontiers in Psychology, 2021)
The main aim of the present study was to compare measured oxygen consumption (Measured-VO2) in a simulated futsal game (S-Game) with the estimated oxygen consumption (Estimated-VO2) through a regression equation between heart rate (HR) and oxygen consumption (VO2) (HR-VO2) in treadmill running, and a secondary aim was to calculate the total energy expenditure (EE) in S-Game. Ten professional players (22.20 ± 3.22 years) were evaluated. HR-VO2 was determined individually in the continuous test on the treadmill (ContTest). The Measured-VO2 in S-Game was compared with the Estimated-VO2 in the ContTest. Alactic and lactic pathways were estimated by VO2. The Estimated-VO2 presented no statistically significant difference with the Measured-VO2, paired test-t (p = 0.38). However, the correlation between Estimated and Measured VO2 was very weak (r = -0.05) and it presented poor agreement (CCC = -0.04). In addition, Bland Altman plot presented bias of -2.8 mL·kg-1·min-1 and individual difference as large as 19 mL·kg-1·min-1. The HR-VO2 determined by the ContTest was not a good individual predictor of VO2. The high intensity and intermittent nature of the futsal game possibly caused dissociation in the HR-VO2 relationship. Continuous test on a treadmill is not recommended for estimating VO2 and calculating individual EE in futsal game. This is recommended only for the group mean. The total EE in S-Game was 13.10 ± 1.25 kcal·min-1 (10.81 ± 1.57 METs). The contribution from the metabolic pathways was: aerobic (93%), alactic (5%), and lactic (2%).